Financial Sector Development and Real Sector Expansion in Nigeria - Iriabije, Alex Oisaozoje; Effiong, Ubong (International Journal of Economics (IJEC), 2025)
This paper examined the effect of financial sector development on the growth of the real sector of the Nigerian economy from 1981 to 2022. Financial sector development was measured using the interest rate spread which measures the intermediation efficiency of the financial system while the growth rate of real gross domestic product was used to capture real sector expansion. The study utilized time series data which were obtained from the World Bank and the Central Bank of Nigeria statistical bulletin. The autoregressive distributed lag model (ARDL) model was utilized for the analysis. Findings from the study indicated that financial sector development exerted a negative and significant effect on economic growth in the short run while the effect becomes positive and significant in the long run. It was concluded that greater interest rate spread arises from high transaction cost associated in financial intermediation in developing economies with infrastructural deficiency. The paper recommended that there is need to further deepen the Nigerian financial system by a narrower interest rate spread. This can be achieved through provision of necessary infrastructure to cut down the transaction costs which are usually factored into the lending rate.